Does Media Discourse Favour the Emergence of Avalanche Risk in Medium-High Mountain Regions? Between Ignorance and Underestimation, the Example of the Vosges Mountains - Florie Giacona; Brice Martin; Nicolas Eckert (Revue de Géographie Alpine)
Despite significant proof to the contrary, scientific and institutional agents present the Vosges Mountains, a medium-high mountain range located in north-eastern France, as a territory that poses almost no risk of avalanches. A comprehensive review of the daily press, as well as national and regional television news, shows that media discourses do not counter this point of view strongly. Indeed, unlike the Alpine environment, whose risk the media presents in a concrete and sometimes pedagogical way, the Vosges Mountains receive very little coverage with respect to risk. More generally, the argumentative strategies that the media use are ambiguous and on the edge between warning about and underestimating the risk. Therefore, the image that is conveyed is one of a territory where the risk is limited to a few locations and/or to particular circumstances. Consequently, avalanches continue to be viewed as a distinctive attribute of a specific space – namely, high mountains – while the question of the danger posed by the Vosges Mountains is left open. This observation should be complemented by a study of the origin of such editorial choices, as well as their impact on the risk representations among different target audiences.